Sikami'n lumad : bagong panitikan ng katutubong Mindanaw - Mindanawon Initiatives for Cultural Dialogue ([Davao City] : Mindanawon Initiatives for Cultural Dialogue, 2005)
Literary collections of indigenous people in Mindanao, Philippines.
Cebuano, Tagalog, and one story in English.
Keywords: Philippine literature -- Indigenous peoples; Literature and anthropology -- Mindanao (Philippines); Lumads (Philippine people) -- Literarcy collections; Indigenous peoples -- Mindanao (Philippines) -- Social life and customs; Mindanao (Philippines) -- Literatures; Mindanao (Philippines) -- Indigenous peoples